Why does armed conflict begin again? A new analytic approach. (October 2018) - Schoon, Eric W
An increasing majority of armed conflicts worldwide are episodes of recurrence (i.e. armed conflicts that occur after another armed conflict ends in the same country). This trend motivates a growing collection of scholarship on the causes of recurrence, but empirical research on this topic supports contradictory conclusions. Engaging these contradictions, this article introduces a novel approach to retroductive comparative analysis, which adapts the logic of semi-structured interviews for use in historical research, to examine the features and causes of 58 cases of armed conflict recurrence that took place between 1946 and 2005. Through this analysis, I identify five varieties of recurrence that are substantively and causally distinct. My analysis identifies scope conditions for existing theories of recurrence and, more broadly, demonstrates how distinct configurations of power inequalities, political opportunities, and the pursuit of legitimacy shape the proximate causes of each variety of recurrence.